2003
DOI: 10.1177/088840640302600405
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and Retaining Culturally and Linguistically Diverse Teachers in Special Education: Models for Successful Personnel Preparation

Abstract: There has been considerable discussion concerning the recruitment and retention of underrepresented groups to the field of Special Education. This dialogue has deepened given the changes in student demographics and the dire shortages of qualified instructional personnel. This article examines specific issues related to recruitment and retention of students who are culturally and linguistically diverse to special education personnel preparation programs. Particular emphasis is placed on strategies that support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Social institutions such as schools should also make attempts to include groups that have been historically marginalized and excluded from equal opportunities in the labor market. In special education, this movement was reflected in IDEA amendments of 1990 and 1997 that called for an increase in the number of underrepresented groups in teacher education programs (Patton et al, 2003). Research shows that the percentage of undergraduates who are students of color has increased from 21% in 1990 to 43% in 2014 (National Center for Education Statistics, n.d.), suggesting that more students of color are attending college but not necessarily entering teaching.…”
Section: Racial Diversity and The Set Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Social institutions such as schools should also make attempts to include groups that have been historically marginalized and excluded from equal opportunities in the labor market. In special education, this movement was reflected in IDEA amendments of 1990 and 1997 that called for an increase in the number of underrepresented groups in teacher education programs (Patton et al, 2003). Research shows that the percentage of undergraduates who are students of color has increased from 21% in 1990 to 43% in 2014 (National Center for Education Statistics, n.d.), suggesting that more students of color are attending college but not necessarily entering teaching.…”
Section: Racial Diversity and The Set Workforcementioning
confidence: 99%
“…We focused on SETs in California because the state serves the largest and one of the more racially diverse special education populations in the country. Using data on all teachers with special education credentials over the last 18 years, this study is one of the first to document changes in the racial composition of the SET workforce over an extended period and assess whether calls for SET diversity during previous amendments of IDEA have succeeded (Patton et al, 2003). We also extend previous work that has examined the distribution of SET quality in high-poverty schools (Mason-Williams, 2015), by simultaneously assessing the extent of variation in SET qualifications at the school, district, and county levels.…”
mentioning
confidence: 99%
“…These include: (a) salaries in higher education are not competitive with market salaries (Cora-Bramble, 2006;Lopez, 2007;Phillips, 2002); (b) universities must make an active commitment by the administration (DumasHines, Cochran, & Williams, 2001;Spencer, 2003); (c) a low number of candidates is prevalent (Castle & Arends, 2003;Phillips, 2002); (d) minority faculty feel isolated (Lopez, 2007;Patton, Williams, Floyd, & Cobb, 2003); (e) there is a lack of formalized mentoring programs (Dumas-Hines, Cochran, & Williams, 2001;Subervi & Cantrell, 2007); (f) minority faculty face increased work loads (often resulting from minority faculty becoming the minority "experts" and being placed on many committees dealing in part or whole with minority issues) (Dooley, 2003); and, (h) minority faculty feel unable to effect change (Lopez, 2007).…”
Section: Recruitment Of Minority University Facultymentioning
confidence: 98%
“…This issue is compounded when one investigates the realm of special education (Barnett, Gibson, & Black, 2003;Dooley, 2003;Patton, Williams, Floyd, & Cobb, 2003;Tyler, Cantou-Clarke, Easteling, & Klepper, 2003) and recruitment and retention of minority faculty in bilingual special education is even a more perilous task (Ortiz & Yates, 2002;Smith, Tyler, Easterling, Smith-Davis, Clarke & Mims, 2000;U.S. Department of Education, 1998).…”
mentioning
confidence: 97%
“…In their review of recruitment and retention strategies for diverse teachers, Patton, Williams, Floyd, and Cobb (2003) described critical features of successful programs: setting goals and objectives for recruitment, providing programs to sensitize faculty to diversity and issues that affect minority students, the use of peer support in the form of cohorts, and providing academic support and flexibility in the programs of study. They revealed that early field experiences, strong collaborative efforts with public schools, orientation programs to help students adjust to campus life, and efforts to recruit and attract minority faculty were also factors of successful programs.…”
Section: Changes In the Children Youth And Families We Servementioning
confidence: 99%